Control Systems with Saturating Inputs Analysis Tools and Advanced Design - Corradini, Maria Letizia; Cristofaro, Andrea; Giannoni, Fabio; Orlando, Giuseppe; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
This series aims to report new developments in the fields of control and information sciences - quickly, informally and at a high level. The type of material considered for publication includes: 1. Preliminary drafts of monographs and advanced textbooks 2. Lectures on a new field, or presenting a new angle on a classical field 3. Research reports 4. Reports of meetings, provided they are a) of exceptional interest and b) devoted to a specific topic. The timeliness of subject material is very important.
Introduction -- Estimation of the null controllable region: Continuous-time plants -- Estimation of the null controllable region: Discrete-time plants -- Control Design Issues: Continuous-time plants -- Control Design Issues: Discrete-time plants.
Keywords: Engineering; Engineering design; Industrial engineering; Engineering; Control; Engineering Design; Industrial and Production Engineering